Mathematical Critical Thinking and Learning Experiences of Junior High School Students: A Preliminary Needs Assessment for FJIMEC–GeoGebra–Scratch Model Development - Ardi Dwi Susandi; Yumiati Yumiati; Endang Wahyuningrum; Sudirman Sudirman; Nia Jusniani; Hasan Basri (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Despite decades of curriculum reform, persistent gaps in Indonesian mathematics education remain. Students are taught mathematics formally, yet consistently fail to demonstrate higher-order reasoning abilities. Both national and international assessments confirm that mathematical critical thinking skills encompassing the ability to evaluate arguments, investigate claims, and draw logical conclusions remain a critical weakness, particularly at the junior high school level. This situation is further compounded by the minimal use of digital technologies such as GeoGebra and Scratch in everyday classroom instruction. This study conducted a preliminary investigation into the mathematical critical thinking abilities and mathematics learning experiences of Grade VIII students in Cirebon Regency (West Java) and Pamekasan Regency (East Java), serving as the empirical foundation for the development of the FJIMEC (Focusing, Justifying, Investigating, Messaging, Evaluating, Concluding) instructional model integrated with GeoGebra and Scratch. Using a convergent parallel mixed-methods design, the study involved 128 students and four mathematics teachers. The critical thinking test results were concerning: mean scores of 41.2 for Cirebon and 39.8 for Pamekasan, with 84.4% of students falling in the low category. The weakest indicators were Evaluating and Concluding. The Mann-Whitney U test revealed no significant between-region difference (p = 0.412), indicating a systemic deficit. Questionnaire analysis revealed low technology utilization (M = 2.43/5.00) and high mathematics anxiety. These findings provide preliminary empirical support for developing a FJIMEC–GeoGebra–Scratch instructional model.